Mental suffering and academic performance in Psychology students at Sergipe (Research, Society and Development, 2021)
The purpose of the work was to identify the correlation between academic performance and mental suffering of Psychology students from higher education institutions in Sergipe. The research was carried out during the covid-19 pandemic, in an exploratory cross-sectional study model from March 8 to April 22, 2021 with the application of a self-completed form containing questions about sociodemographic data, self-assessment of academic performance and adaptation of the Self-Report Questionnaire (SRQ-20). The study included a sample of 264 Psychology students from 5 higher education institutions in Sergipe. During data analysis, associations between variables were tested using the T test of independent samples performed using IBM SPSS Statistics Base 20.0. The prevalence of individuals with signs of psychological distress was 70.5%, it was possible to conclude in view of the results, which are risk factors for mental distress: being female, having a frequency equal to or less than 80%, GPA equal or less that 8 points, failing at least one discipline, being dissatisfied with the chosen course, having thought of dropping out of the course, finally, a negative self-assessment about academic performance. These results will be important to support actions aimed at prevention and mental health care in the academic life of psychology students.